2010
DOI: 10.1109/lmwc.2010.2040218
|View full text |Cite
|
Sign up to set email alerts
|

60 GHz Double-Balanced Gate-Pumped Down-Conversion Mixers With a Combined Hybrid on 130 nm CMOS Processes

Abstract: Two 60-GHz compact double-balanced gate-pumped mixers using standard bulk 0.13 m CMOS process are presented. The homodyne and heterodyne mixers utilize small-size combined hybrids and demonstrated a small chip size of 0.8 0.85 and 0 7 0 7 mm 2 , including pads. With 5 dBm LO power, the best measured conversion gains are 1 and 0 dB in the 3 dB bandwidths of 15 GHz from 54 to 69 GHz and 14 GHz from 53 to 67 GHz RF. The LO-to-RF isolations are greater than 45 dB at a low bias of 1.2 V and 12 mA. This is the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…These mixers showed good isolation between RF and LO ports associated with high power consumption which make these Gilbert-cell mixers not suitable for low power and low-voltage applications (Wang & Tsai, 2009). In contrast, the double-balanced gate mixers exhibit low supply voltage and low dc consumption (Lien et al, 2010). Compared to other double-balanced mixers, these mixers show low LO power, low noise figure and high conversion gain, and they have better isolations than the single-balanced gate mixers (Lien et al, 2010).…”
Section: Mixersmentioning
confidence: 99%
See 1 more Smart Citation
“…These mixers showed good isolation between RF and LO ports associated with high power consumption which make these Gilbert-cell mixers not suitable for low power and low-voltage applications (Wang & Tsai, 2009). In contrast, the double-balanced gate mixers exhibit low supply voltage and low dc consumption (Lien et al, 2010). Compared to other double-balanced mixers, these mixers show low LO power, low noise figure and high conversion gain, and they have better isolations than the single-balanced gate mixers (Lien et al, 2010).…”
Section: Mixersmentioning
confidence: 99%
“…In contrast, the double-balanced gate mixers exhibit low supply voltage and low dc consumption (Lien et al, 2010). Compared to other double-balanced mixers, these mixers show low LO power, low noise figure and high conversion gain, and they have better isolations than the single-balanced gate mixers (Lien et al, 2010). The design in shows a 60-GHz quadrature balanced single-gate mixer implemented in 130 nm CMOS technology.…”
Section: Mixersmentioning
confidence: 99%
“…The design procedure of the rat-race hybrid in [10, 11] is also complex. A combined hybrid is proposed in [12], but that double-balanced architecture still occupies a large area and has high dc power consumption. Moreover, the design considerations and procedures of a single-balanced gate-pumped mixer have not been described in detail in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] adopt various baluns to implement MMW mixers. A low-loss and high-isolation hybrid combiner is used for a gate-driven V-band mixer [5]. In this Letter, a Darlington-pair topology is employed to improve the cutoff frequency f T of the CMOS transistor.…”
mentioning
confidence: 99%
“…Introduction: Since the demand for low cost, high integration and high data-rate short-range wireless communication applications is progressively increasing, many studies of millimetre-wave (MMW) integrated circuits (ICs) have been reported [1][2][3][4][5]. To operate in MMW bands (Ka, V and W bands), advanced CMOS technologies such as 90/65/ 40 nm nodes are the prior choice to implement for the MMW ICs.…”
mentioning
confidence: 99%